Plasma and muscle tissue disposition of enrofloxacin in Nile tilapia (Oreochromis niloticus) after intravascular, intraperitoneal, and oral administrations - Corum, Orhan; Terzi, Ertugrul; Durna Corum, Duygu; Tastan, Yigit; Gonzales, Ruby C.; Kenanoglu, Osman Nezih; Arriesgado, Dan M.; Navarro, Victor R.; Bilen, Soner; Sonmez, Adem Yavuz; Uney, Kamil (Informa UK Limited, 2022)
The aim of the study was to investigate the plasma and muscle pharmacokinetic of enrofloxacin (ENR) and its active metabolite ciprofloxacin (CIP) in Nile tilapia (Oreochromis niloticus) following single intravascular (IV), intraperitoneal (IP), or oral (PO) administration at 30 ± 1 °C. In this study, 234 healthy Nile tilapia (120-150 g) were used. The fish received a single IV, IP, or PO treatment of ENR at a dose of 10 mg/kg. The plasma and muscle tissue concentrations of ENR and CIP were measured using high-performance liquid chromatography with fluorescence detection and were evaluated using non-compartmental analysis. The elimination half-life, volume of distribution at steady state, and total body clearance of ENR were 21.7 h, 2.69 L/kg, and 0.09 L/h/kg, respectively. The peak plasma concentrations of ENR after IP or PO administration were 6.11 and 4.21 µg/mL at 0.25 and 2 h, respectively. The bioavailability of ENR for IP or PO routes was 78% and 86%, respectively. AUC(0-120)muscle/AUC(0-120)plasma ratios following the IV, IP, or PO administrations were 1.43, 1.49, and 1.07, respectively. CIP was detected after all routes, but the AUC0-last ratios of CIP to ENR were <1.0% for plasma and muscle. ENR was detected up to 120 h following the IV, IP, or PO administrations. The long residence time of ENR after single IV, IP, or PO administration ensured the plasma concentration was ≥1 × MIC for bacteria with threshold MIC values of 0.92, 0.72, and 0.80 μg/mL over the whole 120 h observed. However, further studies are necessary to determine the optimum pharmacokinetic/pharmacodynamics data of ENR for the treatment of infections caused by susceptible bacteria in tilapia.
Keywords: Enrofloxacin; Bacteria; Muscles; Administration, Oral; Cichlids; Ciprofloxacin; Animals; Fluoroquinolones; Half-Life